Impairment of cerebrovascular reactivity in response to hypercapnic challenge in a mouse model of repetitive mild traumatic brain injury. Issue 6 (June 2021) - Lynch, Cillian E; Eisenbaum, Maxwell; Algamal, Moustafa; Balbi, Matilde; Ferguson, Scott; Mouzon, Benoit; Saltiel, Nicole; Ojo, Joseph; Diaz-Arrastia, Ramon; Mullan, Mike; Crawford, Fiona; Bachmeier, Corbin
Incidences of repetitive mild TBI (r-mTBI), like those sustained by contact sports athletes and military personnel, are thought to be a risk factor for development of neurodegenerative disorders. Those suffering from chronic TBI-related illness demonstrate deficits in cerebrovascular reactivity (CVR), the ability of the cerebral vasculature to respond to a vasoactive stimulus. CVR is thus an important measure of traumatic cerebral vascular injury (TCVI), and a possible in vivo endophenotype of TBI-related neuropathogenesis. We combined laser speckle imaging of CVR in response to hypercapnic challenge with neurobehavioral assessment of learning and memory, to investigate if decreased cerebrovascular responsiveness underlies impaired cognitive function in our mouse model of chronic r-mTBI. We demonstrate a profile of blunted hypercapnia-evoked CVR in the cortices of r-mTBI mice like that of human TBI, alongside sustained memory and learning impairment, without biochemical or immunohistopathological signs of cerebral vessel laminar or endothelium constituent loss. Transient decreased expression of alpha smooth muscle actin and platelet-derived growth factor receptor β, indicative of TCVI, is obvious only at the time of the most pronounced CVR deficit. These findings implicate CVR as a valid preclinical measure of TCVI, perhaps useful for developing therapies targeting TCVI after recurrent mild head trauma.